The Effectiveness of Family Support on Utilizing Basic Immunization Services In Posyandu Bambu Village Mamuju - I Kadek Dwi Swarjana; Dewarawati Patandean (Alta Dharma Publisher, 2021)
Efforts to prevent the transmission and transmission of dangerous infectious diseases in children, especially those under five years of age. Immunization is a form of health intervention that is very effective in reducing infant and under-five mortality rates. However, the achievement of the global target of 1 in 5 children in the world is recorded that they have not received routine immunization. This study aims to determine the description of family support by utilizing basic immunization service facilities. Methods: This study used an analytic survey design with a cross sectional study approach. Sampling by purposive sampling. The data collection technique was done by using a questionnaire. The sample in this study were 100 subjects who met the inclusion criteria. Results: The study shows that from the statistical analysis test using the SPSS version 16.0 program, it shows that 51.0% of the mother's family support is good, 37.0% is sufficient. Meanwhile, using posyandu service facilities showed 72.0%. Conclusion: This shows that there is a relationship between family support and the use of basic immunization services at posyandu with a significance level of ? = 0.031.